Aspectos ecofisiológicos da catingueira e do pinhão-bravo em uma área de caatinga de Sergipe - Costa, Nara de Farias (2014)
The difference in rainfall throughout the year is a recurring problem that the plants in the field must contend as a result of the moments of drought to which they can be submitted. In the Caatinga, this problem is even greater, since the rains are very sparse and irregular, causing drought for months. The plants of the Caatinga have several adaptations to resist such conditions. This work aimed to evaluate physiological parameters of two endemic species of the Caatinga, the |catingueira| (Poincianella pyramidalis) and |pinhão-bravo| (Jatropha mollissima), in search to discover what strategies these species adopt to survive the drought. Two collections, one in the dry season and one in the wet, were made to evaluate parameters of water relations, concentrations of organic solutes and photosynthetic pigments, chlorophyll a fluorescence and gas exchange. The |catingueira| shown to have been damaged by drought, with a significant reduction in their rates of water relations, particularly in the relative water content, which reached values below 60%, and the performance indices of chlorophyll a fluorescence. The |pinhão-bravo| was able to maintain their high tissue turgor, but the rates of fluorescence and net photosynthesis demonstrated that he was affected by drought since their photosynthetic parameters suffered very significant reductions.